Ecosystem-specific controls of denitrifier gene abundance and community composition on potential nitrous oxide emissions in upland and paddy soils - Xianchu Su; Guiping Ye; Hang-Wei Hu; Mengmeng Feng; Luyuan Sun; Yuheng Cheng; Zi-Yang He; Jia Liu; Yongxin Lin (Soil Ecology Letters, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Seismic rehabilitation of severely earthquake-damaged ductile RC T-shaped beams using mechanically anchored CFRP strips: Anchorage requirements and experimental validation - Chien-Kuo Chiu; Yi-Feng Lin; Hsin-Fang Sung; Lung-Cheng Hsieh (Engineering Structures, 2026)

SERS sensing platform based on MIL-100(Fe)@AgNPs for norepinephrine/adenosine monitoring in patient plasma - Peng Zhao; Kai Liu; Yueyan Li; Xiaofang Ban; Yuheng Wu; Jiaqi Liu; Xiaohong Wu; Ziyi Cheng; Fan Wang; Shuo Li; Feng Lin; Huifang Tang; et al. (Analytica Chimica Acta, 2026)

Divergent activation of a glutathione-tryptophan module by cysteine and hydrogen sulfide enables metabolic recovery from cyanide poisoning in rice - Yi Kang; Xing-Hui Feng; Cheng-Zhi Li; Yu-Juan Lin; Xiao-Zhang Yu (Journal of Environmental Chemical Engineering, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

Synergistic magneto-aeration photocatalysis over AgI/TiO2/mrGO composite for high-salinity recalcitrant wastewater - Chunxia Zhao; Bingqian Wei; Feng Lin; Hongyang Xue; Yuxin Li; Miaomiao Cheng; Hongjie Wang (Chemical Engineering Journal, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

Infragravity oscillations in a coupled-basin marina under typhoon conditions: physical model experiments and numerical modeling - Shih-Feng Su; Chia-Hsuan She; Jia-Lin Chen; Chen-Hsun Wei; Zhi-Cheng Huang (Ocean Engineering, 2026)

Change detection-based machine learning for earthquake-triggered landslide identification in complex mountain landscapes - Lin Wang; Limin Zhang; Feng Cheng; Xiwei Fan; Shuang Li (Geomorphology, 2026)

Coupled effect of crack inclination and microstructure on the mechanical behavior of soils - Zhao-Lin Cai; Yu-Jun Cui; Chao-Sheng Tang; Qing Cheng; Zhi-Xiong Zeng; Xin-Lun Ji; Tao Wang; Hao Wang; Hai Wang; Jun-Feng Ren (Engineering Geology, 2026)

See and destroy bacterial spores: Visual detection and in situ inactivation using a terbium-porphyrin nanoplatform - Shan Sun; Ke Cheng; Jiayi Feng; Hongbo Juan; Kefeng Zhou; Mingyan Zhao; Heng Zhang; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Palmitic acid-evoked PKR/JNK activation and SIRT1 decline: Association with myocardial ageing phenotype changes and partial reversal by inhibitors - Wenxi Li; Guoshun Liu; Shuijin Huang; Tianhai Lin; Cheng Peng; Feng Liu (Tissue and Cell, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Two new chroman derivatives from the desert plant endophytic fungus Lasiodiplodia sp - Wen-Xiang Tao; Jin Ye; Lin-Ping Zhang; Le Zhang; Dong-Yang Liu; Xiu-Feng Yang; Tian-Cheng Ma; Yi Sun; Chang Zhang; Fan-Wei Liu; Ying Chen; Bo Song (Natural Product Research, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Facile preparation of new bidentate quaternary ammonium-type stationary phase for the separation of versatile analytes in hydrophilic interaction liquid chromatography - Xiao-dong Cheng; Kai-feng Tan; Cai-yong Lin; Yun-ping Li; Xue-xin Dai (Analytica Chimica Acta, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Synthesis of visible-light-responsive magnetic recyclable ternary photocatalyst g-C3N4/Bi2O3/Fe3O4 for heavy metal stabilization from municipal solid waste incineration fly ash - Quanming Ren; Zunchao Ren; Feng Lin; Qingsong Zhang; Shuo Feng; Fei Cheng (Journal of Environmental Chemical Engineering, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

Rosa laevigata Michx. as a fermentation adjunct modulates microbial succession, metabolic profiles, and sensory quality of Traditional Hakka Huangjiu during brewing - Lin Cheng; Xin Feng; Yujing Wang; Yifang Chen; Bing Li; Feiliang Zhong; Xuegang Luo (Food Bioscience, 2026)

Tracing the evolution of granitic magmas revealed by fayalite–ferrosilite-bearing microgranular enclaves in Jiuyishan area of South China Block - Jing-Yi Liu; Quan Ou; Jian-Qing Lai; Feng Zi; Kun Wang; Wen-Zhou Xiao; Zhi-Cheng Lin; Cui-Yun Wang; Qian-Cheng Feng; Jia Liao (Acta Geochimica, 2026)

A new sesquiterpene and two new benzoic derivatives from the marine-derived fungus Aspergillus versicolour SCSIO41697 - Qi Cheng; Feng Wu; Keyue Wu; Xumeng Ren; Yiran Lin; Shuhua Qi (Natural Product Research, 2026)

Decoration of the ferritin nanocage surface to regulate the interfacial structure of emulsions for the development of a chitosan-based active film applied to Agaricus bisporus preservation - Kai Lin; Wenjie Zhao; Pengya Du; Suchen Zhao; Cailin Song; Yuanhao Guo; Jinling Cao; Yanfen Cheng; Feier Cheng; Wenfei Zhao; Cuiping Feng; Shaojun Yun (Food Hydrocolloids, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Sources, sinks, and isotopic fractionation of antimony in a karst catchment: constraints on multi-media migration and biogeochemical cycling - Yu Lin; Guangyi Sun; Xinyu Li; Yunjie Wu; Yu Cheng; Heng Yao; Xinbin Feng (Geochimica et Cosmochimica Acta, 2026)

Rab10 GTPase from the mud crab Scylla paramamosain is involved in the host immune response against V. parahaemolyticus infection - Chang-Hong Cheng; Hai-Peng Qin; Si-Gang Fan; Hong-Ling Ma; Guang-Xin Liu; Dong-Lin Yao; Wen-Fan Luo; Xian-Feng Yang; Zhi-Xun Guo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Dopamine-mediated plant stress tolerance: from physiological regulation to rhizosphere microbial shaping - Yang Cao; Peihua Du; Fengqing Cheng; Minjuan Lin; Wenchao Du; Yifeng Feng (Plant and Soil, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Biaxial stretching of wet-cast polyoxadiazole films for high-thermal-conductivity graphene films toward cost-effective thermal management - Hao Cheng; Weizhi Lin; Shaopeng Chen; Jing Yu; Feng Chen (Chemical Engineering Journal, 2026)

Antioxidant capability of peanut shell extracts obtained using an ethanol–ammonium sulfate two-phase system - Yung-Sheng Lin; Cheng-Kun He; Yun-En Jian; Ming-Ren Chen; Tz-Feng Lin; Cheng-You Chen; Wei-Hsun Wang (Biomass and Bioenergy, 2026)

The Time Reliable Effect of Probiotic Clostridium butyricum on the Growth of Spotted Sea Bass (Lateolabrax maculatus) - Yiqin Deng; Liwen Xu; Keng Yang; Ziyang Lin; Shujun Zang; Kui Jiang; Wangdong Li; Nabil A. Ibrahim; Hongling Ma; Changhong Cheng; Juan Feng (Probiotics and Antimicrobial Proteins, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Cadmium accumulation and isotope fractionation in soil–oilseed rape (Brassica napus L.) system in a typical Karst region - Weihai Yu; Guangyi Sun; Heng Yao; Xian Wu; Zhe Liu; Yu Lin; Yu Cheng; Jiang Li; Hua Zhang; Xinbin Feng (Journal of Hazardous Materials, 2026)

Hydrothermal extraction and characterization of hemicellulose from biomass as a natural emulsifier - Yilin Li; Shuo Jiang; Zhiyuan Xu; Yixiang Xu; Seunghee Yoon; Xuanbo Liu; Yifan Cheng; Sean F. O'Keefe; Jactone Ogejo; Feng Lin; Yiming Feng; Haibo Huang (Food Chemistry, 2026)

Alternating current or direct current: Which is better for electrochemical membrane separation water purification system? - Zhen Qiu; Jiujing Xu; Cheng Chen; Wei Yu; Bisheng Li; Liguo Shen; Bing Yu; Huajun Feng; Hongjun Lin (Chemical Engineering Journal, 2026)

Identification of Mitochondria-Related Genes Associated with Stroke Risk Through Multi-omics Summary Data-Based MR Analysis - Xiaorong Tang; Guannan Cheng; Siyun Chen; Lulu Yao; Liming Lu; Chenwei Shen; Lubao Feng; Wenwen Zhang; Nenggui Xu; Lin Wang (Molecular Neurobiology, 2026)

Divergent impacts of partial manure substitution on soil nitrous oxide emissions dependent on phosphorus availability - Yuheng Cheng; Jinbo Zhang; Hang-Wei Hu; Xiangyin Ni; Jianbo Fan; Song Wan; Mengmeng Feng; Christoph Müller; Ji-Zheng He; Yongxin Lin (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anomalous transport of colloidal goethite and plutonium in single granite fracture experiments: Modeling and evaluation - Dong-Xu Liu; Qi Cheng; Hao Diao; Liu-Xing Huang; Zeng-Hu Ma; Jian-Feng Lin (Journal of Hydrology, 2025)

Efficient biomass fractionation for levulinic acid production from rice husk - Xi Cheng; Qingge Feng; Dachao Ma; Yuan Qi; Lin Feng; Fanghong Qin; Xiaodie Cheng; Xu Zeng (Journal of Environmental Chemical Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Differential modulation of aroma profiles in instant Oolong tea powder by two Aspergillus niger β-glucosidases - Ziyue Chen; Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Shuyi Weng; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2025)

Techno-economic analysis of cost-competitive hard carbon production from biomass for sodium-ion batteries - Yilin Li; Yixiang Xu; Yifan Cheng; Sean F. O’Keefe; Jactone Ogejo; Feng Lin; Haibo Huang (Bioresource Technology, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Early Cenozoic source to sink relation between the Tula Basin and the surrounding ranges: Insights for the Tibetan Plateau growth - Jingzhen Peng; Feng Cheng; Dehai Zhang; Hongwei Zhou; Maomao Wang; Xiangzhong Li; Zhaojie Guo; A. K. Khudoley; A. S. Tesakov; Lin Wang; Yan Ma (Science China Earth Sciences, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

The Double-Edged Effect of Connexins and Pannexins of Glial Cells in Central and Peripheral Nervous System After Nerve Injury - Yue-Yan Cen; Xin-Lin Gao; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen; Yan-Yan Zhang (Molecular Neurobiology, 2025)

A long-term common garden experiment reveals geocytotype-dependent succession of plant community invaded by Solidago canadensis - Dongyan Feng; Jiliang Cheng; Zhongsai Tian; Xianghong Yang; Lei Lin; Huan Zhang; Zhen Wang; Sheng Qiang (Journal of Plant Research, 2025)

Isolation and Genomic Characterisation of Lymphocystivirus platichthys1 in Brackish‐Water Cultured Spotted Seabass Lateolabrax maculatus in Zhuhai, South China - Hongling Ma; Changhong Cheng; Yiqin Deng; Zhixun Guo; Yong Li; Guangxin Liu; Huajian Lin; Liwen Xu; Juan Feng (Journal of Fish Diseases, 2025)
Lymphocystis disease virus (LCDV) stands as one of the most widespread causative agents affecting a diverse array of teleost globally. According to the literature, LCDV encompasses four species, and Lymphocystivirus paralichthys1 (known as LCDV‐C) has long been regarded as the predominant national epidemic isolate in mainland China. In this study, two instances of severe mass mortalities associated with LCDV in brackish‐water cultured juvenile spotted seabass in Zhuhai, South China, were monitored starting from early April 2023. The death toll in these two cases peaked at approximately 4000 and 10,000 fish per day, respectively, with cumulative mortalities reaching around 70% within 19 days of the disease outbreak. Based on clinical symptoms, histopathological analyses and transmission electron microscopy observations, the diseases were diagnosed as LCDV infections. The virus was isolated using the Mandarin fish fry (MFF‐1) cell line and named LCDV‐ZH04/23. Subsequently, LCDV‐ZH04/23 was roughly purified, and its entire genome was sequenced and annotated. The results indicated that ZH04/23 consists of 102,661 base pairs, encodes 108 putative viral genes and has a G/C content of 29.3%. Genomic collinearity analysis revealed that the whole genome of ZH04/23 exhibits the highest similarity (99.9%) to the well‐known Lymphocystivirus platichthys1 (LCDV‐1) from Europe, but shows significant divergence from the other three LCDV species. Collectively, this study marks the first isolation and characterisation of L. platichthys1 at the whole genome level from cases of severe mass mortalities in pond‐cultured spotted seabass in China. Moreover, it is the first to identify L. platichthys1 as an emerging pathogen in cultured spotted seabass.

A full-ring mechanical model of shield tunnels considering detailed joint configurations - Si-Qi Yang; Huai-Na Wu; Hong-Zhan Cheng; Dong-Lin Feng; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Tribopotential mediated ferroelectric polarization for versatile reconfigurable p–n junction - Keteng Zhang; Jinran Yu; Yichen Wei; Liuqi Cheng; Zhenyu Feng; Jie Gong; Zhong Lin Wang; Qijun Sun (Chemical Engineering Journal, 2025)

Pediatric Abdominal and Pelvic CT Scans and the Subsequent Risk of Malignancy and Benign Genital Tumors: A Retrospective Cohort Study - Feng-Yi Su; Chih-Feng Chen; Kevin Chih-Yang Huang; Cheng-Li Lin; Fuu-Jen Tsai; Jui-Ting Hsu; Shin-Lei Peng (Journal of Medical and Biological Engineering, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Efficient removal of trace diazepam via enhanced peroxymonosulfate activation by 1T-phase and sulfur vacancy-rich MoS2-C-Fe - Jiawei Lin; Hongfeng Zhang; Jingyu Liu; Yongyou Hu; Jiaqi Peng; Feng Xu; Cheng Zhao; Qing Wang; Hao Zhou; Yi Yin (Journal of Cleaner Production, 2025)

The correlation of immunotoxicity with size and chemical properties of particulate matter within macrophages - Hsiang-Yu Kung; Yi-Shiuan Wang; Yung-Jui Chen; Ting-Hsuan Wu; Jai-Yu Chen; Yueh-Feng Wen; Yu-Cheng Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

A review of umami taste of Tea: Substances, perception mechanism, and physiological measurement prospects - Yashu Yu; Xiaoxiao Feng; Imre Blank; Haoli Wang; Yiwen Zhu; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Trends in Food Science & Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Identification of the sources and migration of antimony in karst terraces via Sb stable isotopes - Yunjie Wu; Guangyi Sun; Yu Lin; Xinyu Li; Yu Cheng; Heng Yao; Xinbin Feng (Journal of Hazardous Materials, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Pyrus pyrifolia WRKY31 activates the ribosomal protein gene RPL12 to confer black spot resistance - Xiangyu Cheng; Caihua Xing; Feng Zhang; Likun Lin; Keke Zhao; Huizhen Dong; Xiaosan Huang; Shaoling Zhang (Plant Science, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Application of artificial intelligence in the rapid determination of moisture content in medicine food homology substances - Mengyu Zhang; Boran Lin; Shudi Zhang; Cheng Peng; Chang Li; Tingting Feng; Lian Li; Aoli Wu; Chunguo Yang; Wentian Wang; Shouyao Huang; Lei Nie; et al. (Food Chemistry, 2025)

Supplementation of Akkermansia muciniphila improves diabetic kidney disease by regulating gut microbiome in db/db mice - Zhengzheng Liao; Jian Zhou; Jiaqiang Lin; Yue Zhu; Jing Feng; Zhouyang Cheng; Xiajialong Li; Zhipeng Li; Shaoping Nie (Food Bioscience, 2025)

Synergistic effect of dextran and ergosterol: A venue for fabricating a water-in-oil pickering emulsion gel as a solid fat substitute in cream cheese - Kai Lin; Pengya Du; Pengfei Dong; Yaxin Wang; Yuanhao Guo; Jinling Cao; Yanfen Cheng; Feier Cheng; Wenfei Zhao; Cuiping Feng; Shaojun Yun (Food Hydrocolloids, 2025)

Unravelling the pathogenesis of Vibrio parahaemolyticus infection: impacts on antioxidant and innate immunity gene responses in Scylla paramamosain - Guangxin Liu; Ce Li; Sigang Fan; Hongling Ma; Yiqin Deng; Jianjun Jiang; Changhong Cheng; Juan Feng; Li Lin; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

The landscape of cell lineage tracing - Ye Feng; Guang Liu; Haiqing Li; Lin Cheng (Science China Life Sciences, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

Systematic analysis of associations between obesity and memory decline - Ying Yue Huang; Wei Sen Zhang; Jiao Wang; Chao Qiang Jiang; Feng Zhu; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Lin Xu (GeroScience, 2025)
Despite the development of numerous obesity indicators, the optimal measure associated with memory remains to be elucidated. We examined and compared these associations whilst also exploring potential interactions with education. We analysed the associations between 20 obesity indicators and memory (measured by Delayed Word Recall Test (DWRT)) in middle-aged and older participants from Guangzhou Biobank Cohort Study by linear regression and stratification analyses. We used two-sample Mendelian randomisation (2SMR) to analyse the associations of obesity with cognitive performance. Of 20 obesity indicators, 6 and 7 were associated with poorer memory function measured by baseline and follow-up DWRT; 7 and 10 with faster memory decline measured by mean annual change (MAC) and MAC rate of DWRT. Central obesity measured by waist-to-hip-to-height ratio (WHHR) z -score showed the greatest effect size, with the β s (95% CIs) being − 0.09 (− 0.11 to − 0.07), − 0.07 (− 0.09 to − 0.04), − 0.02 (− 0.03 to − 0.01) and − 0.49 (− 0.69 to − 0.29), respectively. The associations were weaker in those with higher education ( P for education-interaction from 0.008 to 0.049). In 2SMR, body mass index (BMI), waist circumference and BMI-adjusted waist-to-hip ratio were negatively associated with cognitive performance using inverse-variance weighted method, with β s (95% CIs) being − 0.11 (− 0.15 to − 0.07), − 0.07 (− 0.12 to − 0.02) and − 0.06 (− 0.09 to − 0.02), respectively. In conclusion, obesity, especially central obesity measured by WHHR, was associated with poorer memory function and faster memory decline in middle-aged and older people, with a weaker association observed amongst those with higher education. Graphical Abstract

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

New insights into the impact of microplastics on nitrogen transformation in urban rivers based on field experiments - Cheng Yang; Yuanyuan Feng; Jinjiang Duan; Nayin Li; Qingping Zou; Peng Lin; Mengli Chen; Jiang Li; Han Zhang (Journal of Environmental Chemical Engineering, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Determination of the spatiotemporal evolution patterns and obstacle factors of coupling coordination of the water–energy–food–ecology system in Ordos City, China - Jihong Qu; Jixian Lin; Mengting Cheng; Zezhong Zhang; Kai Feng; Fei Wang; Kun Ren; Juan Zhou; Yanbin Li (Environmental Geochemistry and Health, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Seismic performance of grouted CFDST column base: Investigation and design method - Zhi-Cheng Yang; Wei Li; Yu-Feng Cheng; Lin-Hai Han (Engineering Structures, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Exploring anxiolytic peptides derived from walnut protein by an integrated approach of multivariate analysis, random forest methodology - Zishan Hong; Ying Cheng; Mingjie Zhou; Shuguang Wang; Xiaomin Li; Shiyun Feng; Guowan Su; Lin Zheng; Mouming Zhao (Food Bioscience, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Enhancing rejection of short-chain per- and polyfluoroalkyl substances by tailoring the surface charge of nanofiltration membranes - Yue Zhi; Xiaoqing Zhao; Ao Shuai; Yonghui Jia; Xinyi Cheng; Shihong Lin; Feng Xiao; Le Han; Hongxiang Chai; Qiang He; Caihong Liu (Water Research, 2025)

Effect of geosynthetics reinforcement on seismic behavior of coral sand revetment breakwater subjected to mainshock-aftershock sequences - Lin Zhou; Rui Sun; Jian-Feng Chen; Cheng-Zhi Xia; Hua-Ning Wang (Soil Dynamics and Earthquake Engineering, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Synthesis and characterization of fish gelatin hydrogels for enhanced biopolymer applications - Wen-Long Cheng; Shan Shan; Sheng Shu; Guang-Xian Liu; Lin-Feng Yuan; Xiao-Mei Sha; Zong-Cai Tu (Food and Bioproducts Processing, 2025)

Comammox Nitrospira and ammonia-oxidizing bacteria are metabolically active in a subtropical estuarine wetland - Mengmeng Feng; Yongxin Lin; Guiping Ye; Zi-Yang He; Dong Zhu; Hang-Wei Hu; Yuheng Cheng; Fengyi Han; Ping Yang; Ji-Zheng He (Applied Soil Ecology, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Metaproteomics reveals metabolic activities potentially involved in bloom formation and succession during a mixed dinoflagellate bloom of Prorocentrum obtusidens and Karenia mikimotoi - Hua-Min Cheng; Xiao-Lian Ning; Shu-Feng Zhang; Hao Zhang; Lin Lin; Si-Qi Liu; Da-Zhi Wang (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Mechanical properties of a novel fiber-bridging interface for connecting FRP profile and concrete - Hongwei Lin; Haidong Qu; Peng Feng; Huixin Zeng; Guanzhi Cheng (Engineering Structures, 2025)

Comprehensive suitability assessment of fish habitat by integrating mechanism model and bayesian network model - Yuliang Yuan; Ran Li; Jingjie Feng; Hang Wan; Honghui Lin; Xiaolong Cheng (Ecological Engineering, 2025)

Robust photothermal self-healing superhydrophobic composite coating for durable anti/de-icing applications - Jie zhu; Wen Li; Tong Wang; Huimeng Feng; Jia Cheng; Cunguo Lin; Xin Wang; Wei Wang; Shougang Chen (Chemical Engineering Journal, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Lithological impact on topsoil organic carbon storage of karst forest soils shaped by aggregate pool complexity and their molecular composition - Qingmei Lin; Shuotong Chen; Xiao Feng; Thammavongsa Sounilan; Kun Cheng; Xuhui Zhang; Rongjun Bian; Xiaoyu Liu; Yan Wang; Marios Drosos; Jufeng Zheng; Lianqing Li; et al. (Applied Soil Ecology, 2025)

Characteristics, source analysis, and risk assessment of organochlorine pesticide contamination in nearshore surface sediments of a tropical tourist island - Hongbing Wang; Lin Zhang; Feng Yang; Li Yan; Cong Lin; Cheng Shen (Frontiers in Marine Science, 2025)
Surface sediment samples were collected from the surrounding waters of the two largest tourist islands in Sanya, China, to compare and evaluate the sources, distribution, and ecological risks of 21 organochlorine pesticides (OCPs). The total concentration of OCPs ranged from 1.35 to 5.0 ng/g. Among the OCPs, ΣDDTs accounted for the largest proportion, followed by ΣHCHs. The concentrations of HCHs and DDTs from the west side of West Island were significantly higher than those from the east side, and fine-grained sediments exhibited a stronger adsorption effect on OCPs. Source analysis indicated that the area experienced new inputs of HCH pollutants, while historical residues of HCHs remained high. Residual OCPs are still widely present in the environment, transported mainly by river runoff, with a smaller portion originating from atmospheric deposition and ship paints. Ecological risk assessment results showed that factors occasionally causing adverse biological effects include Heptachlor epoxide, 4,4'-DDE, ΣDDT, Dieldrin, Endrin, and γ-HCH, while other factors rarely caused negative biological effects. Potential ecological effect evaluations indicated that stations SY03, SY04, SY06, and SY09 were classified as having moderate ecological effect levels, while other stations were classified as having no ecological effects. Strengthened investigation, monitoring, and control of pollutant sources in ecologically impacted areas are necessary. This study fills a data gap for the region and provides an academic foundation for environmental protection and the sustainable development of tourism resources.

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

The volatile compound (E)-2-hexenal in wampee (Clausena lansium) represses the development of Penicillium italicum and enhances the disease resistance of postharvest citrus fruit - Ce Yang; Zizhen Lin; Ze Luo; Zhiquan Wang; Ping Liu; Rangwei Xu; Feng Zhu; Yunjiang Cheng (Postharvest Biology and Technology, 2025)

Activation of protein kinase B rescues against thapsigargin-elicited cardiac dysfunction through regulation of NADPH oxidase and ferroptosis - Xiaohu Wang; Feng-Juan Li; Yong Cheng; Shuying Chen; Shuyi Zhu; Yingmei Zhang; Russel J. Reiter; Milad Ashrafizadeh; Jie Lin; Guizhen Wang; Ling Lin; Jun Ren (Chemico-Biological Interactions, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

Comprehensive evaluation of air quality: incense burning and night market emissions in Kaohsiung, Taiwan, using the ISCST3 air quality model - Pei-Cheng Cheng; Kassian T. T. Amesho; Yin-Cheng Huang; Yuan-Chung Lin; Feng-Chih Chou; Tsu-Nai Wang; Pei-Shih Chen; Kang-Shin Chen; Ken-Lin Chang; Chien-Hung Lee (Air Quality, Atmosphere & Health, 2025)

Protective Effects of Antcin H Isolated from Antrodia cinnamomea Against Neuroinflammation in Huntington’s Disease via NLRP3 Inflammasome Inhibition - Yu-Jun Chang; Cheng-Hsu Chen; Yi-Chen Chen; Ming-Tse Wu; Ting-Yu Lin; Kuo-Feng Hua; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2024)

First direct measurements of the nitrogen isotopic composition of vehicle tailpipe-emitted NH3 and implications for the source apportionment of NH3 in urban atmosphere - Yu-Ning Feng; Yunhua Chang; Lin Cheng; Haifeng Yu; Jinling Lv; Wendell W. Walters (Science of The Total Environment, 2024)

Paleozoic-Mesozoic multistage tectonic evolution of the North Qilian Shan revealed by detrital zircon U-Pb and fission-track double dating - Xu Lin; Marc Jolivet; Jing Liu-Zeng; Kaige Guan; Feng Cheng; Soares Cleber; Chengwei Hu (Geomorphology, 2024)

The mining of thermostable β-glucosidase for tea aroma enhancement under brewing conditions - Qi Lin; Cheng Peng; Kunpeng Yu; Yanling Lin; Yongquan Xu; Lijun Li; Hui Ni; Feng Chen (Food Chemistry, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Exploration of the flavor diversity of oolong teas: A comprehensive analysis using metabolomics, quantification techniques, and sensory evaluation - Xiaoxiao Feng; Haoli Wang; Yashu Yu; Yiwen Zhu; Jingke Ma; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Food Research International, 2024)

Acrolein exposure affects ovarian function by interfering with glycolysis and mitochondrial energy metabolism in mouse - Yan-Zhu Chen; Wen-Ke Wang; Yi-Fan Yang; Si-Yao Cheng; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Yu Liu (Environmental Pollution, 2024)

Observations of avalanche–substrate interactions in the Iymek rock avalanche deposit: A possible causative mechanism - Anwen Shi; Yufeng Wang; Qiangong Cheng; Qiwen Lin; Zhiyi Feng; Ke He; Fujun Niu; Zhang Song (Engineering Geology, 2024)

Formation Mechanism and Petroleum Geological Significance of (Ferro) Dolomite Veins from Fractured Reservoirs in Granite Buried Hills: Insights from Qiongdongnan Basin, South China Sea - Wei Duan; Cheng-Fei Luo; Lin Shi; Jin-Ding Chen; Chun-Feng Li (Journal of Marine Science and Engineering, 2024)
This study employs logging, petrology, and geochemistry to investigate the characteristics, origin, and hydrocarbon significance of fractures and (ferro) dolomite veins in a buried hill in the Qiongdongnan (QDN) Basin, South China Sea. We show that the study area is mainly characterized by three stages of fracturing with medium-high dipping angles. The orientation of the fractures is mainly NNW–SSE, consistent with the fault system strike formed by the Mesozoic–Cenozoic tectonic activity in the basin. (Ferro) dolomite veins in the fractures can be classified into three stages, all of which can be even observed in individual fractures. The first stage is the powdery crystal dolomite veins grown mainly on the fracture surface, which have the highest strontium isotope values, as well as high contents of the Mg element and extremely low contents of the Fe and Mn elements. The first-stage veins were formed in a relatively open oxidized environment, and the vein-forming fluids exhibit characteristics of mixing formation water and atmospheric freshwater within the fractures. The second stage, involving fine-crystal dolomite veins, was formed in a buried diagenetic environment where groundwater mixed with deep hydrothermal fluids, and contained the highest carbon isotope values, more Fe and Mn elements, and less Mg element than the first stage. The third stage of medium-crystal ankerite veins was formed in the latest stage, with the lowest strontium and oxygen isotope values. This was mainly a result of deep hydrothermal formation in which the rock-forming material formed from the interaction between the hydrothermal fluid and the iron-rich and aluminosilicate minerals in the surrounding granite of the fractures. We conclude that the multi-phase tectonic movements form a massive scale reticulated fracture inside the granite buried hill, which effectively improves the physical condition of the gas reservoirs. The gas reservoirs remain of high quality, despite the filling of the three stages of (ferro) dolomite veins.

An analytical model of longitudinal joints in the segmental lining of shield tunnels with considering geometric nonlinearity - Dong-Lin Feng; Huai-Na Wu; Ren-Peng Chen; Si-Qi Yang; Hong-Zhan Cheng (Tunnelling and Underground Space Technology, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

An emerging quaternary semiconductor nanoribbon with gate-tunable anisotropic conductance - Shaolong Jiang; Fuchen Hou; Shengfeng Zeng; Yubo Zhang; Erding Zhao; Yilin Sun; Liyun Zhao; Cheng Zhang; Mengyuan Jia; Jun-Feng Dai; Mingyuan Huang; Qing Zhang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genome sequencing analysis and validation of infestation-related functional genes of Vibrio parahaemolyticus LG2206 isolated from the hepatopancreas of diseased mud crab (Scylla paramamosain) in South China - Liu Guangxin; Liu Guangfeng; Li Ce; Ma Hongling; Deng Yiqin; Cheng Changhong; Jiang Jianjun; Fan Sigang; Feng Juan; Lin Li; Qin Zhendong; Guo Zhixun (Fish & Shellfish Immunology, 2024)

Reducing target reliability index of concrete bridge beams through compression yielding - Lin Feng; Yu-Fei Wu; Bing-Cheng Guo; Xiao-Xu Huang (Engineering Structures, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Enhancing typhoon wave hindcasting with random forests and BP neural networks in the SWAN model - Cheng Chen; Hongkun Lin; Dawei Guan; Feng Cai; Qiaoyi Wang; Qingchun Liu (Frontiers in Marine Science, 2024)
Forecasting typhoon waves during typhoons is crucial. In this paper, the numerical wave model SWAN was enhanced through integration with two machine learning methods: the Back Propagation Neural Network and Random Forest. This integration facilitated the development of two distinct models, namely SWAN-BP and SWAN-Tree. Through correlation analysis, key input features were identified for the machine learning models. The forecasts from the SWAN model were subsequently utilized as inputs to enhance further wave prediction. These hybrid models were validated using data from Typhoon Doksuri (2023) and Typhoon Nesat (2017). The results indicated significant improvements in predicting typhoon-induced wave heights with both the SWAN-BP and SWAN-Tree models compared to the original SWAN model. Specifically, the SWAN-BP model demonstrated a 33% improvement in accuracy for the Typhoon Doksuri, whereas the SWAN-Tree model exhibited a 24% improvement. For Typhoon Nesat, the accuracy improvements were 23% for the SWAN-BP model and 21% for the SWAN-Tree model. These findings demonstrate that integrating wave numerical models with machine learning techniques can significantly enhance the predictive accuracy of numerical models. This approach offers a cost-effective means to improve the existing wave forecasting database. Traditionally, the direct use of meteorological and oceanographic data for typhoon wave prediction might be compromised by biases inherent in the numerical wave models. However, the SWAN-BP and SWAN-Tree models effectively reduce these biases, thereby providing more accurate and robust predictions. In conclusion, this paper enhances the predictive accuracy of the SWAN model and establishes a crucial foundation for more precise typhoon wave forecasting through the application of machine learning techniques.

Identification of organic constituents on atmospheric particulate matter in the East Asian background air of free troposphere by GC×GC-TOFMS - Chang-Feng Ou-Yang; Yi-Jun Chen; Hsin-Cheng Hsieh; Chung-Te Lee; Kai-Hsien Chi; Neng-Huei Lin; Chih-Chung Chang; Jia-Lin Wang (Chemosphere, 2024)

A systematic review and meta-analysis on the root effects and toxic mechanisms of rare earth elements - Chenyi He; Yiping Feng; Yirong Deng; Longyong Lin; Sheng Cheng (Chemosphere, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Climate synergistic benefits: A path to the Beautiful China through total control of major air pollutants - Xi Cheng; Zhong-Xing Zhang; Ting Shi; Nian Yang; Shu-Hao Yang; Jian-Lin Chen; Guo-Zhu Mao; Ze-Feng Qi; Sheng Rao; Chun-Lai Jiang (Journal of Cleaner Production, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

Glycosylation of a ferritin nanocage with dextran as a novel emulsifier for the construction of dual-compartmental pickering emulsions to co-encapsulate hydrophobic bioactive compounds - Guo Yuanhao; Wang Yaxin; Dong Pengfei; Wang Shengnan; Lin Kai; Hou Jiangyan; Cui Fangming; Bi Shuyu; Cao Jinling; Cheng Yanfen; Cheng Feier; Yun Shaojun; et al. (Journal of Food Engineering, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Deciphering the formation of granules by n-DAMO and Anammox microorganisms - Zhi-Cheng Zhao; Ruo-Lin Li; Sheng-Qiang Fan; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Environmental Research, 2024)

Warming enhanced the interaction effects of fungi and fungivores and soil potassium mineralization in tropical forest - Feng Sun; Guanzhao Yan; Wei Lin; Wei He; Xianli Cheng; Yingwen Li; Akash Tariq; Jordi Sardans; Josep Penuelas; Jinchuang Wang; Mei Wang; Yuelin Li; et al. (CATENA, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Fluvoxamine Exerts Sigma-1R to Rescue Autophagy via Pom121-Mediated Nucleocytoplasmic Transport of TFEB - Chun-Yu Lin; Hsiang-En Wu; Eddie Feng-Ju Weng; Hsuan-Cheng Wu; Tsung-Ping Su; Shao-Ming Wang (Molecular Neurobiology, 2024)
Expansion of the GGGGCC-RNA repeat is a known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), which currently have no cure. Recent studies have indicated the activation of Sigma-1 receptor plays an important role in providing neuroprotection, especially in ALS and Alzheimer’s disease. Nevertheless, the mechanisms underlying Sigma-1R activation and its effect on (G 4 C 2 )n-RNA-induced cell death remain unclear. In this study, we demonstrated that fluvoxamine is a Sigma-1R agonist that can increase chaperone activity and stabilize the protein expression of Pom121 in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells, leading to increased colocalization at the nuclear envelope. Interestingly, fluvoxamine treatment increased Pom121 protein expression without affecting transcription. In C9orf72 -ALS, the nuclear translocation of TFEB autophagy factor decreased owing to nucleocytoplasmic transport defects. Our results showed that pretreatment of NSC34 cells with fluvoxamine promoted the shuttling of TFEB into the nucleus and elevated the expression of LC3-II compared to the overexpression of (G 4 C 2 ) 31 -RNA alone. Additionally, even when used alone, fluvoxamine increases Pom121 expression and TFEB translocation. To summarize, fluvoxamine may act as a promising repurposed medicine for patients with C9orf72 -ALS, as it stabilizes the nucleoporin Pom121 and promotes the translocation of TFEB in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells.

A highly sensitive SERS substrate of porous membrane-Ag NPs for kidney cancer detection - Sheng Chen; Jiamin Gao; Hongyi Zhang; Li Liu; Feng Lin; Zaijun Cheng; Yanping Chen; Dongyu Guo; Xingen Gao; Juqiang Lin (Analytica Chimica Acta, 2024)

Arbuscular mycorrhizal fungi reduce soil N2O emissions by altering root traits and soil denitrifier community composition - Tangqing He; Wei Lin; Shuo Yang; Jiaqi Du; Bhoopander Giri; Cheng Feng; Frank S. Gilliam; Fuliang Zhang; Xiaoquan Zhang; Xuelin Zhang (Science of The Total Environment, 2024)

Antiadhesive, antibacterial, and anti-inflammatory sandwich-structured ZIF8-containing gauze for enhanced wound healing - Xinghai Wu; Cheng Wang; Jia Wang; Yuchen Feng; Yunpeng Zhu; Yijia Pan; Yifan Yuan; Chenhui Chen; Junyan Cao; Jixing Lin; Xian Tong; Yuncang Li; et al. (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Nitrogen fertilization modulates rice phyllosphere functional genes and pathogens through fungal communities - Wei-Feng Wu; Xin-Yuan Li; Song-Can Chen; Bing-Jie Jin; Chun-Yan Wu; Gang Li; Cheng-liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Science of The Total Environment, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Water-in-oil Pickering emulsion using ergosterol as an emulsifier solely - Yaxin Wang; Yuanhao Guo; Pengfei Dong; Kai Lin; Pengya Du; Jinling Cao; Yanfen Cheng; Feier Cheng; Shaojun Yun; Cuiping Feng (Food Research International, 2024)

Stabilizing high-Ni cathodes with gradient surface Ti-enrichment - Wenchang Zhu; Xiaotian Zhu; Jizhen Qi; Junyi Yao; Yanbin Shen; Guanjian Cheng; Xue Huang; Shiqi Yang; Hao Zhang; Chao-Lung Chiang; Yan-Gu Lin; Jianming Bai; et al. (Chemical Engineering Journal, 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Secondary infections may cause host mortality by inhibiting NRF1-mediated antiviral immune responses - Xu Feng-Lin; Wang Cheng-Qiang; Yin Cheng-Ming; Sun Ya-Nan; Cao Xiao-Tong; Lan Jiang-Feng (Aquaculture, 2024)

Enhanced photodegradation of pentafluoropropionic acid (PFPA) via TiO2-synthetic zeolite composites: A sustainable approach for effective defluorination - Subham Halder; Feng-Chih Chou; Tsz-Kin Wan; Yi-Tien Tsai; Pei-Cheng Cheng; Yuan-Chung Lin (Journal of Water Process Engineering, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Distinctive shear zones demonstrate pervasive laminar cataclastic flow throughout the gigantic Iymek rock avalanche - Anwen Shi; Yufeng Wang; Qiangong Cheng; Qiwen Lin; Tianhua Li; Zhiyi Feng; Ke He; Fujun Niu; Zhang Song (Geomorphology, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

Higher stochasticity in comammox Nitrospira community assembly in upland soils than the adjacent paddy soils at a regional scale - Mengmeng Feng; Yongxin Lin; Zi-Yang He; Hang-Wei Hu; Shengsheng Jin; Jia Liu; Song Wan; Yuheng Cheng; Ji-Zheng He (Science of The Total Environment, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Self-synthesis and performance analysis of a Cu-Fe composite ZSM-5 zeolitic catalyst for NOx reduction and particulate matter removal using NH3 SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Pei-Cheng Cheng; Shang-Cyuan Chen; Yuan-Chung Lin (Journal of Environmental Chemical Engineering, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Integration of bulk-surface charge polarization and active site manipulation for highly efficient photocatalytic aerobic oxidation of sulfides - Jun Wan; Yang-Ai Ma; Yina Nie; Junhao Cheng; Chengming Wang; Lin Liu; Feng Fu (Chemical Engineering Journal, 2024)

Frequency Domain Analysis of Hamstring Activation During Jump-Landing Performance by Athletes with Diverse Training Regimens - Amornthep Jankaew; Yih-Kuen Jan; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2024)

Wind-driven hydrodynamic characteristics of Lake Taihu, a large shallow lake in China - Zongpu Xue; Wei Zhu; Lin Cheng; Yi Lv; Ganyu Feng (Environmental Science and Pollution Research, 2024)

Toward sustainable development of tuna longline fishery in Taiwan: Value chain analysis - Wen-Hong Liu; Chih-Cheng Lin; Cheng-Feng Lee; Chien-Shu Tsai; Tsung-Yu Yang (Marine Policy, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Phthalate esters and nonylphenol concentrations correspond with microplastic distribution in anthropogenically polluted river sediments - Ming-Huang Wang; Chih-Feng Chen; Frank Paolo Jay B. Albarico; Shan-Lu Lin; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Sedimentary provenance constraints on the Cretaceous to Cenozoic palaeogeography of the western margin of the Jianghan Basin, South China - Xu Lin; Jing Liu-Zeng; Marc Jolivet; Weiming Liu; Feng Cheng; Haijin Liu; Lingling Li; Jixin Chen; Chengwei Hu; Xiaokang Chen (Gondwana Research, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Flexible metal membrane integrated electrified and catalytic attributes for multifunctional water purification with enhanced scaling resistance - Ning Kong; Liguo Shen; Qianqian Zeng; Cheng Chen; Jiaheng Teng; Feng Chen; Hongjun Lin (Chemical Engineering Journal, 2024)

A Numerical Study of Moisture and Ionic Transport in Unsaturated Concrete by Considering Multi-ions Coupling Effect - Zhaozheng Meng; Yufei Zhang; Wei-kang Chen; Chuan-qing Fu; Qing Xiang Xiong; Cheng-lin Zhang; Qing-feng Liu (Transport in Porous Media, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Hierarchical Y zeolite with accessible intracrystalline mesopores and enhanced hydrocracking performances via sequential multi-carboxyl acid and fluoroborate post-treatments - Lin-Jiao Wei; Peng Peng; Ke Qiao; Guang-Nan Cheng; Ubong Jerome Etim; Zi-Feng Yan (Fuel, 2023)

Pathological observation and transcriptomic analysis of thymus injury in PRRSV-infected piglets - Naying Su; Zhengdan Lin; Xi Liu; Xiuxiu Sun; Xinxin Jin; Helong Feng; Cunlin Zhan; Xueying Hu; Changqin Gu; Wanpo Zhang; Guofu Cheng (Veterinary Research Communications, 2023)
The thymus, the central immune organ in mammals, plays an important role in immune defense. Porcine reproductive and respiratory syndrome virus (PRRSV) infection in piglets can cause thymus injury and immunosuppression. However, the mechanisms of thymus injury remain unknown. This study was aimed at investigating the specific manifestations of thymus injury through the construction of a PRRSV-infected piglet model and histopathological observation. In this study, fourteen 40-day-old PRRSV-free piglets were randomly divided into two groups, eleven of which were intramuscularly injected with 3 mL of PRRSV WUH3 virus suspension (10 6 PFU /mL) in the infection group, and three of which were sham-inoculated with 3 mL of RPMI-1640 medium in the control group. Clinical necropsy and samples collection were performed on day 8 after artificial infection. With the Illumina platform, the transcriptomes of piglet thymus tissues from infected and control piglets were sequenced to explore the relationships of differentially expressed genes (DEGs) and signaling pathways with thymus injury. The immune organs of PRRSV-infected piglets were severely damaged. The histopathological findings in the thymus indicated that PRRSV infection was associated with a large decrease in lymphocytes, cell necrosis and cell apoptosis; an increase in blood vessels and macrophages; thymic corpuscle hyperplasia; and interstitial widening of the thymic lobules. The transcriptomic analysis results revealed that the Gene Ontology functions of DEGs were enriched primarily in biological processes such as angiogenesis, regulation of angiogenesis and positive regulation of cell migration. Moreover, greater numbers of blood vessels and macrophages were observed in the thymus in PRRSV-infected than control piglets. KEGG pathway enrichment analysis revealed that the DEGs were significantly enriched in the Toll-like receptor signaling pathway, chemokine signaling pathway, IL-17 signaling pathway and TNF signaling pathway. The expression of TLR8, IRF5, the chemokines CCL2, CCL3L1 and CCL5; and their receptors CCR1, CCR2 and CCR5 was significantly up-regulated in PRRSV infection, thus suggesting that these cytokines were associated with the pathological processes of thymus injury.

Correction: Improved Brassica oleracea JZS assembly reveals significant changing of LTR‑RT dynamics in different morphotypes - Xu Cai; Jian Wu; Jianli Liang; Runmao Lin; Kang Zhang; Feng Cheng; Xiaowu Wang (Theoretical and Applied Genetics, 2023)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Accumulated Hepatic Steatosis Grades Predicted by T2*-IDEAL Fat Fraction - Chang-Hsien Liu; Hing-Chiu Chang; Yi-Jui Liu; Wei-Ching Lin; Chi-Feng Hsieh; Te-Pao Lin; Cheng-Hsuan Juan; William Tzu-Liang; Chun-Jung Juan (Journal of Medical and Biological Engineering, 2023)

Novel insights into molecular signatures and pathogenic cell populations shared by systemic lupus erythematosus and vascular dementia - Jing Chen; Xiao’feng Zhao; Cheng Huang; Jia’xing Lin (Functional & Integrative Genomics, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

Immune-microenvironment modulatory polyurethane-hyaluronic acid hybrid hydrogel scaffolds for diabetic wound treatment - Yuan Feng; Kecen Xiao; Jinlin Chen; Jingjing Lin; Yuanyuan He; Xueling He; Fuyi Cheng; Zhen Li; Jiehua Li; Feng Luo; Hong Tan; Qiang Fu (Carbohydrate Polymers, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Performance analyses of two-phase closed thermosyphons for road embankments in the high-latitude permafrost regions - Guan-fu Wang; Chuang Lin; Long Zhu; De-cheng Feng; Yang-yang Xin; Feng Zhang (Journal of Mountain Science, 2023)

Acoustic Field Radiation Prediction and Verification of Underwater Vehicles under a Free Surface - Yung-Wei Chen; Cheng-Cheng Pan; Yi-Hsien Lin; Chao-Feng Shih; Jian-Hong Shen; Chun-Ming Chang (Journal of Marine Science and Engineering, 2023)
This study aimed to examine the acoustic field radiated by propellers and underwater vehicles. For the verification of sound radiation in underwater vehicles, numerical methods are widely used in addition to experiments and propeller blade frequencies for calculation and validation. Numerical convergence and accuracy are more important for near-field and far-field problems. This paper uses the boundary element method (BEM) to assess the convergence of the finite volume method (FVM). In this study, the FVM, including the Reynolds-averaged Navier–Stokes method and the Ffowcs Williams–Hawkings (FW-H) acoustic model, is used to investigate the influence of various geometric inflows on the hydrodynamic and noise performance of the propeller. Then, the sound radiation of the FVM is compared with the BEM at the far field to determine the number of meshed elements. Furthermore, spectral analysis is being conducted to examine the noise generated by the underwater vehicle and propeller. The objective is to investigate the influence of the free surface on propeller efficiency. After verifying the numerical simulation, the results indicate that a relationship can be established between water pressure and propeller thrust under specific conditions. This relationship can be used to estimate the magnitude of propeller thrust at different water depths. The simulated results of propeller thrust, torque coefficient, propulsion efficiency, and sound radiation in this study are consistent with experimental values. This demonstrates the accuracy and practicality of the findings of numerical procedures in engineering applications.

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Surface fabrication of silica aerogels from inorganic precursor achieving elastic and superhydrophobic sponges for oil-water separation - Xiang Li; Xiaoxiao Huang; Qingge Feng; Zheng Liu; Dongbo Wang; Dachao Ma; Lin Feng; Chen Zuo; Junyi Liu; Sinan Wang; Zhuoyan Huang; Xiaodie Cheng; et al. (Journal of Environmental Chemical Engineering, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Bond behavior of FRP-concrete wet-bonding interface under lateral confinement - Hongwei Lin; Huixin Zeng; Peng Feng; Cheng Jiang; Yuqing Zhang (Engineering Structures, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Twisting two-dimensional photothermal sponges for boosting solar steam generation - Feng Lu; Shao-Lin Wu; Lu-Na Quan; Zhi-Hui Zhong; Hao-Cheng Yang; Ming Xue (Chemical Engineering Journal, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Evidence for the Late Pliocene Aridification in the Eastern Tarim Basin, Northwest China - Hua Zhang; Feng-Lin Lü; Cheng-Lin Liu; Peng-Cheng Jiao; Hui-Jing Yin; Hui Yan; Bao-Cheng Ma; Liang-Liang Zhao; Hong-Chao Liu (Journal of Earth Science, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

PbrWRKY70 increases pear (Pyrus bretschneideri Rehd) black spot disease tolerance by negatively regulating ethylene synthesis via PbrERF1B-2 - Caihua Xing; Qiming Chen; Qinghai Qiao; Shenao Gu; Xiangyu Cheng; Huizhen Dong; Likun Lin; Feng Zhang; Chenyang Han; Zan Zhang; Hao Yin; Kaijie Qi; et al. (Plant Science, 2023)

Open-framework hybrid zinc/tin selenide as an ultrafast adsorbent for Cs+, Ba2+, Co2+, and Ni2+ - Yang Liu; Feng-Qi Shi; Xin Hao; Meng-Yu Li; Lin Cheng; Cheng Wang; Kai-Yao Wang (Journal of Hazardous Materials, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Ammoniated straw incorporation increases maize grain yield while decreasing net greenhouse gas budget on the Loess Plateau, China - Jinchao Li; Yue Li; Zhipeng Yang; Yanxin Fang; Cheng Li; Yulong Shi; Nanping Lin; Qinge Dong; Kadambot H.M. Siddique; Hao Feng; Naijiang Wang (Agriculture, Ecosystems & Environment, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Updates on applications of low-viscosity grade Hydroxypropyl methylcellulose in coprocessing for improvement of physical properties of pharmaceutical powders - Cheng Jin; Fei Wu; Yanlong Hong; Lan Shen; Xiao Lin; Lijie Zhao; Yi Feng (Carbohydrate Polymers, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Biodegradation of sulfametoxydiazine by Alcaligenes aquatillis FA: Performance, degradation pathways, and mechanisms - Yuqian Du; Qilu Cheng; Mingrong Qian; Yangzhi Liu; Feng Wang; Junwei Ma; Xin Zhang; Hui Lin (Journal of Hazardous Materials, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Improved bioremediation of PCDD/Fs contaminated soil by mycelium-free liquids induced by agro-industrial residues - Chih-Yu Cheng; Zhi-Feng Zhang; Acharee Kaewlaoyoong; Jing-Ting Huang; Nicholas Kiprotich Cheruiyot; Chitsan Lin; Hung-Chou Huang (Bioresource Technology Reports, 2023)

An improved YOLOv5s method based bruises detection on apples using cold excitation thermal images - Peijie Lin; Hua Yang; Shuying Cheng; Feng Guo; Lijin Wang; Yaohai Lin (Postharvest Biology and Technology, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

High altitude Pliocene to Pleistocene vegetation and climate change of the Kunlun Pass Basin, NE Tibetan Plateau - Florian Schwarz; Ulrich Salzmann; Feng Cheng; Jian Ni; Junsheng Nie; Megan R. Patchett; Xiangzhong Li; Lin Li; John Woodward; Carmala Garzione (Global and Planetary Change, 2023)

Fragility analysis of nuclear power plant structure under real and spectrum-compatible seismic waves considering soil-structure interaction effect - Feng Cheng; Jianbo Li; Lei Zhou; Gao Lin (Engineering Structures, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Effectiveness of Combined Exercise and Physiotherapy Intervention in Improving Functional Activity of Patients with Knee Osteoarthritis in Muslim Pray Movements - Rakhmad Rosadi; Po-Ting Wu; Yu-Lin You; Li-Chieh Kuo; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2023)

Effects of pollutant toxicity on the eyes of aquatic life monitored by visual dysfunction in zebrafish: a review - Xiao-Fan Chen; Zhi-Cheng Lin; Zenghua Qi; Zongwei Cai; Zhi-Feng Chen (Environmental Chemistry Letters, 2023)

Identifying spatial agglomeration and driving forces of land use by green industries: a case study of Jiangsu Province, China - Qi Wang; Xiao-feng Zhao; Sheng-Hau Lin; Xian-jin Huang; Jian-cheng Lv (Environmental Science and Pollution Research, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Cytotoxic steroidal glycosides from the rhizomes of Paris polyphylla var. yunnanensis - Yang Liu; Mei-You Liu; Lin-Lin Bi; Yun-Yuan Tian; Peng-Cheng Qiu; Xiao-Ying Qian; Min-Chang Wang; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Phytochemistry, 2023)

Miocene rapid strike-slip faulting along the Altyn Tagh Fault, North Tibet: Insight from sedimentology records in the Tula and Qaidam basins - Zhongcheng Zeng; Lin Wang; Peng Wang; Zenglin Hong; Feng Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Plastic film-mulched ridges and straw-mulched furrows increase soil carbon sequestration and net ecosystem economic benefit in a wheat-maize rotation - Xiaoqi Luo; Cheng Li; Nanping Lin; Naijiang Wang; Xiaosheng Chu; Hao Feng; Haixin Chen (Agriculture, Ecosystems & Environment, 2023)

Hypoxia triggers the proliferation of antibiotic resistance genes in a marine aquaculture system - Yiqin Deng; Jianjun Jiang; Yinbang Huang; Changhong Cheng; Ziyang Lin; Guangxin Liu; Zhixun Guo; Juan Feng (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

A conductive hydrogel based on nature polymer agar with self-healing ability and stretchability for flexible sensors - Zhen Nie; Kelin Peng; Lizhi Lin; Jueying Yang; Zhekun Cheng; Qiang Gan; Yu Chen; Changgen Feng (Chemical Engineering Journal, 2023)

Regulating desolvation and homogenized ion flux towards highly reversible dendrite-free zinc anode - Xin Qi; Fuli Xie; Yu-Ting Xu; Hai Xu; Cheng-Lin Sun; Sheng-Han Wang; Jian-Yong Hu; Xiao-Feng Wang (Chemical Engineering Journal, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

The largest rock avalanche in China at Iymek, Eastern Pamir, and its spectacular emplacement landscape - An-Wen Shi; Yu-Feng Wang; Qian-Gong Cheng; Qi-Wen Lin; Tian-Hua Li; Bernd Wünnemann (Geomorphology, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

A microfluidic immunosensor based on magnetic separation for rapid detection of okadaic acid in marine shellfish - Yuxiang Ji; Gaozhe Cai; Cheng Liang; Zehang Gao; Weimin Lin; Zizhen Ming; Shilun Feng; Hongwei Zhao (Analytica Chimica Acta, 2023)

Experimental Study on Pyrolysis of Rice Straw Catalyzed by CaO/Al2O3-Phosphate Mixture - Lianlian Xu; Zhongwen Xu; Feng Zhang; Yinmei Yuan; Bin Cheng; Chuang Zhang; Ping Chen; Xiangyong Huang; Yuyu Lin; Mingyan Gu (BioEnergy Research, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Nitrogen Enrichment Reduces the Diversity of Bacteria and Alters Their Nutrient Strategies in Intertidal Zones - Yuan-Feng Xu; Xu-Meng Dong; Cheng Luo; Shuo-Nan Ma; Ji-Lin Xu; Yong-De Cui (Frontiers in Marine Science, 2022)
Intertidal ecosystems are affected by severe nitrogen (N) pollution as a result of anthropogenic activities, and it is unclear how this may affect intertidal microbial communities, which play critical roles in regulating biogeochemical cycles. To address this gap, we conducted a two-month mesocosm experiment using six targeted concentrations of total N. The findings indicated that N entering seawaters has direct negative effects on the bacterial diversity. Dose dependence was found for the effects of N on bacterial diversity in sediment: low N addition increased the bacterial diversity, but a reduction in bacterial diversity occurred when N exceeded a certain value (≥ 3 mg L−1). Additionally, N enrichment caused clear shifts in bacterial community composition with increases in the relative abundance of Balneola (organic-degrading), Phalacroma mitra (carbohydrate-fermenting), and Bacteroides (phosphorus (P)-solubilizing), and decreases in Leptolyngbya_PPC_6406 (N2-fixing). The increased abundance in P-solubilizing and organic-degrading bacteria and decrease in N-fixing bacteria, combined with the upregulated activity of alkaline phosphatase and downregulation of urease activity, implied that the bacterial assemblage tended to be more effective in P and carbon acquisition but reduced N acquisition. Further path analysis suggested that N had direct effects on bacteria and contributed 50%–100% to the variations in bacterial diversity, whereas environmental changes such as dissolved oxygen and pH played minor roles. Overall, bacteria occurring in sediment were likely more stress-resistant to high N exposure than those occurring in seawater, possibly due to the high buffering capacity of sediment and growth tolerances of bacteria in the sediment. These findings point to the vulnerability of microbes in water systems to increasing global N loading, and that N reduction is needed to combat the loss of microbial diversity.

Effects of micronized bamboo powder on growth performance, serum biochemical indexes, cecal chyme microflora and metabolism of broilers aged 1–22 days - Fawen Dai; Tao Lin; Lumin Cheng; Jian Wang; Jianjun Zuo; Dingyuan Feng (Tropical Animal Health and Production, 2022)
Adding insoluble fiber to diet of broilers has been reported to improve intestinal health and promote growth performance. Bamboo powder is a cheap raw material with rich insoluble fiber. This study aims to explore the effects of feeding micronized bamboo powder (MBP) on growth performance, serum biochemical indexes, intestinal microflora, and metabolism of broilers. A total of 1440 1-day-old slow-growing Ephedra chickens were randomly divided into three groups considering gender and body weight: (1) Group D: feeding with basal diet without antibiotics; (2) Group E: feeding with basal diet supplemented with 5% rice bran (RB); (3) Group F: feeding with basal diet supplemented with 1% MBP. Each group involved 8 replicates feeding for 22 days, with 60 chickens per replicate. Various indexes were detected. For the growth performance, the weight gain and feed consumption ratio (G: F) of Group F supplemented with MBP is 0.57 ± 0.04, which is significantly higher than that of E group supplemented with RB (0.52 ± 0.01, P < 0.05). For the serum biochemical indexes, the glutathione peroxidase activity in Group F is significantly higher than that of Group D, while the malondialdehyde content is significantly lower than that of Group D and Group E ( P < 0.05 for all). The fresh cecal chyme is taken for determination. In Group F, the α diversity index Faith_pd is significantly lower in Group F than that of Group D. The microorganism species in cecal chyme of Group F and Group E are also different. The metabolic pathways of Group F, mainly in fatty acid metabolism, amino acid metabolism and intestinal immune IgA production, were different from those of Group D and Group E. Adding 1% MBP to broiler diet can enhance the anti-oxidant capacity, improve chyme microflora, regulate the metabolism pathways responsible for intestinal fatty acids, amino acids, and immunity.

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Comparison of different inversion methods of D-T2 two-dimensional nuclear magnetic resonance logging and applicability analysis - Cheng-Lin Li; Mao-Jin Tan; Ke-Wen Wang; Feng Zhou; Ying-Ming Liu; Hai-Tao Zhang; Li-Zhi Xiao (Applied Geophysics, 2022)

A bi-scale assessing framework for aesthetic ecosystem services of villages in a world heritage site - Yin-ping Ding; Zhi-lin Liu; Yuan-mei Jiao; Qiu-e Xu; Kan-feng Zhang; Cheng-jing Liu; Fan Chen (Journal of Mountain Science, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Circ_0020093 ameliorates IL-1β-induced apoptosis and extracellular matrix degradation of human chondrocytes by upregulating SPRY1 via targeting miR-23b - Mingli Feng; Lin Jing; Jingbo Cheng; Shuai An; Jiang Huang; Qi Yan (Molecular and Cellular Biochemistry, 2021)
Osteoarthritis (OA) is a chronic disease characterized by articular cartilage degeneration and uncontrolled chondrocyte apoptosis. At present, accumulating evidence introduces that circular RNA (circRNA) is involved in the development of OA. The aim of our study was to explore the role and the functional mechanism of circ_0020093 in OA cell model. Human chondrocytes were treated with interleukin-1 beta (IL-1β) to construct OA model. The expression of circ_0020093, miR-23b, and Sprouty 1 (SPRY1) mRNA was measured by quantitative real-time polymerase chain reaction (qRT-PCR). Cell apoptosis was assessed by flow cytometry assay. The expression of extracellular matrix (ECM)-associated markers and SPRY1 protein level was detected by qRT-PCR and Western blot. Bioinformatics analysis-predicted relationship between miR-23b and circ_0020093 or SPRY1 was further verified by dual-luciferase reporter assay and RNA pull-down assay. In this study, we found that the expression of circ_0020093 and SPRY1 was declined, while miR-23b expression was elevated in IL-1β-treated chondrocytes. IL-1β induced chondrocyte apoptosis and ECM degradation, while these negative effects were alleviated by circ_0020093 overexpression or miR-23b inhibition. MiR-23b was a target of circ_0020093, and SPRY1 was a downstream target of miR-23b. Rescue experiments showed that miR-23b enrichment reversed the role of circ_0020093 overexpression, and SPRY1 knockdown also reversed the effects of miR-23b inhibition. Importantly, circ_0020093 positively regulated SPRY1 expression by targeting miR-23b. In conclusion, circ_0020093 ameliorates IL-1β-induced apoptosis and ECM degradation of human chondrocytes by regulating the miR-23b/SPRY1 axis.

Effects of Fatigue on Inter-joint Coordination in Ballet Dancers During a Ballet Jumping Movement (petit échappé sauté) - Chai-Wei Lin; Jeng-Feng Yang; Yi-An Chen; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2021)

Novel Dicistroviruses in an Unexpected Wide Range of Invertebrates - Ruo-Lin Cheng; Xiao-Feng Li; Chuan-Xi Zhang (Food and Environmental Virology, 2021)

3D Step-by-step inversion strategy for audio magnetotellurics data based on unstructured mesh - San Cheng; Zhi-Yong Zhang; Feng Zhou; Man Li; Hui Chen; Fu-Sheng Shi; Lin-Pin Huang; Yong Li (Applied Geophysics, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

In-Situ Seawater Gamma Spectrometry with LaBr3 Detector at a Nuclear Power Plant Outlet - Daowei Dou; Zhi Zeng; Wen Yu; Ming Zeng; Wu Men; Feng Lin; Hao Ma; Jianping Cheng; Junli Li (Journal of Marine Science and Engineering, 2021)
In a nuclear emergency, the application of in situ spectrometers for monitoring environmental radioactivity is significantly important, as information on the type and activity of radionuclides released from the accident can be obtained quickly. However, in emergency environmental radiological monitoring, a balance between energy resolution and detecting efficiency must be considered in selecting an appropriate detector. In this study, in situ gamma spectrometry was conducted with the LaBr3 detector to determine the radioactivity of seawater at the discharging outlet of a coastal nuclear power plant in southeast China. The results show that the LaBr3 scintillator has excellent energy resolution and detection efficiency, making it a promising detector for emergency monitoring.

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

N6-methyladenine DNA Demethylase ALKBH1 Regulates Mammalian Axon Regeneration - Qiao Li; Cheng Qian; Harry Feng; Tyger Lin; Qingsan Zhu; Ying Huang; Feng-Quan Zhou (Neuroscience Bulletin, 2021)

Quantitative characterization of horizontal well production performance with multiple indicators: a case study on the Weiyuan shale gas field in the Sichuan Basin, China - Rongze Yu; Wei Guo; Lin Ding; Meizhu Wang; Feng Cheng; Xiaowei Zhang; Shangwen Zhou; Leifu Zhang (Frontiers of Earth Science, 2021)

Experiments on granular flow behavior and deposit characteristics: implications for rock avalanche kinematics - Kun Li; Yu-Feng Wang; Qi-Wen Lin; Qian-Gong Cheng; Yue Wu (Landslides, 2021)

Genome-wide identification and expression analysis of the MADS-box transcription factor family in Camellia sinensis - Zai-Bao Zhang; Yuan-Jin Jin; Hou-Hong Wan; Lin Cheng; Zhi-Guo Feng (Journal of Applied Genetics, 2021)

Impact factors of the accumulation, migration and spread of antibiotic resistance in the environment - Zibo Lin; Tao Yuan; Lai Zhou; Sen Cheng; Xu Qu; Ping Lu; Qiyan Feng (Environmental Geochemistry and Health, 2021)

The molecular mechanism of a novel derivative of BTO-956 induced apoptosis in human myelomonocytic lymphoma cells - Yu-Lin Li; De-Jun Zhou; Zheng-Guo Cui; Lu Sun; Qian-Wen Feng; Shahbaz Ahmad Zakki; Yusuke Hiraku; Cheng-Ai Wu; Hidekuni Inadera (Apoptosis, 2021)

Simulation of the fragmentation and propagation of jointed rock masses in rockslides: DEM modeling and physical experimental verification - Qi-wen Lin; Qian-Gong Cheng; Yu Xie; Feng-shou Zhang; Kun Li; Yu-feng Wang; Yuan-yuan Zhou (Landslides, 2021)

Phylogeny, recombination, and invasiveness of group B Streptococcus revealed by genomic comparisons of its global strains - Enze Lin; Shengmei Zou; Yue Wang; Chien-Chung Lee; Cheng-Hsun Chiu; Ye Feng (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

ARF4 regulates shoot regeneration through coordination with ARF5 and IAA12 - Miao Miao Zhang; Huan Kai Zhang; Jun Feng Zhai; Xian Sheng Zhang; Ya Lin Sang; Zhi Juan Cheng (Plant Cell Reports, 2021)

Chronic Neck Pain Affects Shoulder Muscle Activity and Postural Control During Functional Reach - Cheng-Chieh Lin; Cheng-Feng Lin; Shiang-Hua Hua; Jen-Chieh Liao (Journal of Medical and Biological Engineering, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Comparison of the Nutritional Quality of Three Edible Tissues from Precocious and Normal Adult Female Chinese Mitten Crabs ( Eriocheir sinensis ) - Huafeng Cheng; Haoran Wu; Feng Liang; Mengtian Ge; Shaotong Jiang; Lin Lin; Jianfeng Lu (Journal of Aquatic Food Product Technology, 2021)

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

Concurrent increases in post-pacing action potential duration and contractility predict occurrence of ventricular arrhythmia - Chih-Min Liu; Feng-Zhi Lin; Yao-Chang Chen; Yung-Kuo Lin; Yen-Yu Lu; Cheng-I Wu; Satoshi Higa; Shih-Ann Chen; Yi-Jen Chen (Pflügers Archiv - European Journal of Physiology, 2020)

Doxorubicin metabolism moderately attributes to putative toxicity in prodigiosin/doxorubicin synergism in vitro cells - Shian-Ren Lin; Chun-Shu Lin; Ching-Cheng Chen; Feng-Jen Tseng; Tsung-Jui Wu; Lebin Weng; Ching-Feng Weng (Molecular and Cellular Biochemistry, 2020)
Doxorubicin (Dox) is a widely neoplasm chemotherapeutic drug with high incidences of cardiotoxicity. Prodigiosin (PG), a red bacterial pigment from Serratia marcescens , has been demonstrated to potentiate Dox’s cytotoxicity against oral squamous cell carcinoma cells through elevating Dox influx and identified as a Dox enhancer via PG-induced autophagy; however, toxicity of normal cell remains unclear. This study is conducted to evaluate putative cytotoxicity features of PG/Dox synergism in the liver, kidney, and heart cells and further elucidate whether PG augmented Dox’s effect via modulating Dox metabolism in normal cells. Murine hepatocytes FL83B, cardio-myoblast h9c2, and human kidney epithelial cells HK-2 were sequentially treated with PG and Dox by measuring cell viability, cell death characteristics, oxidative stress, Dox flux, and Dox metabolism. PG could slightly significant increase Dox cytotoxicity in all tested normal cells whose toxic alteration was less than that of oral squamous carcinoma cells. The augmentation of Dox cytotoxicity might be attributed to the increase of Dox-mediated ROS accumulation that might cause slight reduction of Dox influx and reduction of Dox metabolism. It was noteworthy to notice that sustained cytotoxicity appeared in normal cells after PG and Dox were removed. Taken together, moderately metabolic reduction of Dox might be ascribed to the mechanism of increase Dox cytotoxicity in PG-induced normal cells; nevertheless, the determination of PG/Dox dose with sustained cytotoxicity in normal cells needs to be comprehensively considered.

Improved Brassica oleracea JZS assembly reveals significant changing of LTR-RT dynamics in different morphotypes - Xu Cai; Jian Wu; Jianli Liang; Runmao Lin; Kang Zhang; Feng Cheng; Xiaowu Wang (Theoretical and Applied Genetics, 2020)

WDR5a functions in cadmium-inhibited root meristem growth by regulating nitric oxide accumulation in Arabidopsis - Yu Zhang; Yang-Yang Tian; Lin-Feng Wang; Yun-Hui Li; Ting-Ting Li; Wen-Cheng Liu (Planta, 2020)

How do Biotic and Abiotic Factors Regulate Soil Enzyme Activities at Plot and Microplot Scales Under Afforestation? - Qianxi Li; Ji Chen; Jiao Feng; Junjun Wu; Qian Zhang; Wei Jia; Qiaoling Lin; Xiaoli Cheng (Ecosystems, 2020)

Characterization of a Protease Hyper-Productive Mutant of Bacillus pumilus by Comparative Genomic and Transcriptomic Analysis - Yong-Cheng Liu; Lin-Li Han; Tian-Yu Chen; Yan-Bing Lu; Hong Feng (Current Microbiology, 2020)

A calculation model to assess the crack propagation length of rock block in clastic flow - Yang Liu; Yong You; Jin-feng Liu; Shu-xi Zhao; Dong-xu Yang; Dao-chuan Liu; Lin Liu; Yan-fang Xie; Kai-cheng Yang (Journal of Mountain Science, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Impact of Prolonged Tablet Computer Usage with Head Forward and Neck Flexion Posture on Pain Intensity, Cervical Joint Position Sense and Balance Control in Mechanical Neck Pain Subjects - Cheng-Chieh Lin; Siang-Hua Hua; Cheng-Li Lin; Chih-Hsiu Cheng; Jen-Chieh Liao; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2020)

Alzheimer’s Disease and Diabetes: Insulin Signaling as the Bridge Linking Two Pathologies - Jonathan Chang-Cheng Shieh; Pai-Tsang Huang; Yung-Feng Lin (Molecular Neurobiology, 2020)

The roles of moisture transports in intraseasonal precipitation during the preflood season over South China - Qu‐cheng Chu; Qi‐guang Wang; Guo‐lin Feng (International Journal of Climatology, 2020)
The roles of moisture sources and transport in intraseasonal precipitation variabilities during the preflood season over South China are complex and different. In this paper, ERA‐Interim reanalysis data that were collected four times daily from 1979 to 2017 are used to analyse the variation and influence of moisture transport in intraseasonal precipitation during the preflood season over South China. Using the Hybrid Single‐Particle Lagrangian Integrated Trajectory model, fixed atmospheric moisture sources are defined: land area source (LD source), Indian Ocean source (IO source), Pacific Ocean source (PO source), South China Sea source (SCS source), and South China source (SC source). Sea source moisture transport accounts for more than 75% of the total precipitation during the preflood season, which is the most important moisture source in South China. For April, southeasterly moisture transport, which includes PO source and SCS source moisture transports, is the major moisture transport over South China. Then, the IO source and SCS source precipitation increased significantly during May. During June, the IO source precipitation accounted for 43.75% of the total precipitation, thus dominating precipitation over South China. In addition, there is a significant difference in the interdecadal variation in the preflood season precipitation before and after the Indian summer monsoon onset. Before the Indian summer monsoon onset, the land‐sea thermal contrast decreased, which led to a significant interdecadal reduction in the IO source, PO source, and SCS source moisture transports. After the Indian summer monsoon onset, the increase in IO source moisture transport is the primary cause of the interdecadal increase in precipitation over South China.

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Adult sacrococcygeal teratoma: a retrospective study over eight years at a single institution - Xiang-ming Xu; Feng Zhao; Xiao-fei Cheng; Wei-xiang Zhong; Jing-peng Liu; Wei-qin Jiang; Xiao-kai Yu; Jian-jiang Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Anthropometric Database of the Preschool Children from 2 to 6 Years in Taiwan - I-Fang Cheng; Li-Chieh Kuo; Chien-Ju Lin; Hsiao-Feng Chieh; Fong-Chin Su (Journal of Medical and Biological Engineering, 2019)

The complete maternal mitochondrial genome of Acuticosta chinensis (Bivalvia: Unionoida: Unionidae) - Qishuo Wang; Lin Li; Cheng Wang; Cuizhen Wei; Ruijuan Feng; Jing Huang (Conservation Genetics Resources, 2019)

Hydromechanical behavior of radially multilayered cylinders under time-varying loads - Feng Zhou; Zhu Song; Cheng Lin (Marine Georesources & Geotechnology, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Characterization of the complete mitogenome for the freshwater shrimp Exopalaemon modestus - Qishuo Wang; Ruijuan Feng; Lin Li; Cheng Wang; Chuankun Zhu (Conservation Genetics Resources, 2018)

The complete maternal mitochondrial genome sequence of Cuneopsis heudei (Bivalvia: Unionoida: Unionidae) - Qishuo Wang; Lu Ma; Lin Li; Ruijuan Feng; Huan Mu; Xin Wang; Cheng Wang; Xuepeng Wang (Conservation Genetics Resources, 2018)

Analyzing Influencing Factors of Rural Poverty in Typical Poverty Areas of Hainan Province: A Case Study of Lingao County - Jinping Zhang; Feng Zuo; Yanmei Zhou; Mengxiao Zhai; Lin Mei; Yidi Fu; Yeqing Cheng (Chinese Geographical Science, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

Calpain inhibition attenuates bleomycin-induced pulmonary fibrosis via switching the development of epithelial-mesenchymal transition - Yuan Liu; Bing Liu; Gu-qin Zhang; Jing-feng Zou; Meng-lin Zou; Zhen-shun Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

First report of cucumber mosaic virus infecting Arachis hypogaea in Jiangxi Province in China - Feng Zhu; Yan Ping Che; Yang Kai Zhou; Shi Chang Cheng; Zheng Liu; Zhao Lin Ji (Journal of Plant Pathology, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

A fine-grained perspective on the robustness of global cargo ship transportation networks - Peng Peng; Shifen Cheng; Jinhai Chen; Mengdi Liao; Lin Wu; Xiliang Liu; Feng Lu (Journal of Geographical Sciences, 2018)

Assessment of Land Subsidence and Climate Change Impacts on Inundation Hazard in Southwestern Taiwan - Hsiao‐Wen Wang; Cheng‐Wei Lin; Chun‐Yao Yang; Chung‐Feng Ding; Hwung‐Hweng Hwung; Shih‐Chun Hsiao (Irrigation and Drainage, 2018)
Excessive extraction of groundwater resulting in serious land subsidence as well as intensified rainfall and storm surges due to climate change complicate the flooding problems in southwest Taiwan. A coupled set of different models was proposed to analyze the effect of inundation risk considering land subsidence and climate change. Three models, including the groundwater flow model, land subsidence model, and the physiographic drainage–inundation model, were used in this study, enabling simulations of different considerations. The results revealed that more severe flooding would result from land subsidence and climate change. The findings of a 21% increase in flood area with an inundation depth greater than 1.5 m for 200‐yr return period events clearly showed more severe flooding would result from land subsidence. The flooding in those severely subsiding areas would increase in a range from 3.4 to 21.5% when further considering climate change. While the simulation results revealed that the flood area could be decreased by as much as 50% taking into account the implemented policies, the coastal region would still be exposed to a high risk of being flooded. It thus suggests that policies focusing on infrastructure would be insufficient, and river basin management as well as spatial planning should be investigated further. Copyright © 2018 John Wiley & Sons, Ltd.

Genome sequencing and heterologous expression of antiporters reveal alkaline response mechanisms of Halomonas alkalicola - Lei Zhai; Jiuyan Xie; Yafang Lin; Kun Cheng; Lijiang Wang; Feng Yue; Jingyan Guo; Jiquan Liu; Su Yao (Extremophiles, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Characterization of the complete chloroplast genome of the Chinese cherry Prunus pseudocerasus (Rosaceae) - Ying Feng; Tao Liu; Xiao-Yu Wang; Bin-Bin Li; Cheng-Lin Liang; Yu-Liang Cai (Conservation Genetics Resources, 2018)

Nature and origin of Triassic igneous activity in the Western Qinling Orogen: the Wenquan composite pluton example - Kun-Feng Qiu; Hao-Cheng Yu; Zong-Yang Gou; Zhi-Lu Liang; Jia-Lin Zhang; Rui Zhu (International Geology Review, 2018)

Feature analysis and primary causes of pre-flood season “cumulative effect” of torrential rain over South China - Qu-cheng Chu; Qi-guang Wang; Shao-bo Qiao; Guo-lin Feng (Theoretical and Applied Climatology, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Analysis on velocity distribution and displacement along the profile of a slope using both empirical and analytical methods - Tie-lin Chen; Cheng Zhou; En-long Liu; Feng Dai; Jiao Liu (Journal of Mountain Science, 2017)

Far infrared promotes wound healing through activation of Notch1 signaling - Yung-Ho Hsu; Yuan-Feng Lin; Cheng-Hsien Chen; Yu-Jhe Chiu; Hui-Wen Chiu (Journal of Molecular Medicine, 2017)

Magnesium Ions Promote the Biological Behaviour of Rat Calvarial Osteoblasts by Activating the PI3K/Akt Signalling Pathway - Jian Wang; Xiang-Yu Ma; Ya-Fei Feng; Zhen-Sheng Ma; Tian-Cheng Ma; Yang Zhang; Xiang Li; Lin Wang; Wei Lei (Biological Trace Element Research, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

Observation and modeling on irregular purple soil water infiltration process - Dong-bing Cheng; Lin-yao Dong; Feng Qian; Bei Sun (Journal of Mountain Science, 2017)

A meta‐analysis of fertilizer‐induced soil NO and combined NO +N 2 O emissions - Shuwei Liu; Feng Lin; Shuang Wu; Cheng Ji; Yi Sun; Yaguo Jin; Shuqing Li; Zhaofu Li; Jianwen Zou (Global Change Biology, 2017)
Soils are among the important sources of atmospheric nitric oxide ( NO ) and nitrous oxide (N 2 O), acting as a critical role in atmospheric chemistry. Updated data derived from 114 peer‐reviewed publications with 520 field measurements were synthesized using meta‐analysis procedure to examine the N fertilizer‐induced soil NO and the combined NO +N 2 O emissions across global soils. Besides factors identified in earlier reviews, additional factors responsible for NO fluxes were fertilizer type, soil C/N ratio, crop residue incorporation, tillage, atmospheric carbon dioxide concentration, drought and biomass burning. When averaged across all measurements, soil NO ‐N fluxes were estimated to be 4.06 kg ha −1 yr −1 , with the greatest (9.75 kg ha −1 yr −1 ) in vegetable croplands and the lowest (0.11 kg ha −1 yr −1 ) in rice paddies. Soil NO emissions were more enhanced by synthetic N fertilizer (+38%), relative to organic (+20%) or mixed N (+18%) sources. Compared with synthetic N fertilizer alone, synthetic N fertilizer combined with nitrification inhibitors substantially reduced soil NO emissions by 81%. The global mean direct emission factors of N fertilizer for NO ( EF NO ) and combined NO +N 2 O ( EF c ) were estimated to be 1.16% and 2.58%, with 95% confidence intervals of 0.71–1.61% and 1.81–3.35%, respectively. Forests had the greatest EF NO (2.39%). Within the croplands, the EF NO (1.71%) and EF c (4.13%) were the greatest in vegetable cropping fields. Among different chemical N fertilizer varieties, ammonium nitrate had the greatest EF NO (2.93%) and EF c (5.97%). Some options such as organic instead of synthetic N fertilizer, decreasing N fertilizer input rate, nitrification inhibitor and low irrigation frequency could be adopted to mitigate soil NO emissions. More field measurements over multiyears are highly needed to minimize the estimate uncertainties and mitigate soil NO emissions, particularly in forests and vegetable croplands.

Occurrence and photodegradation of methylmercury in surface water of Wen-Rui-Tang River network, Wenzhou, China - Shuihong Pan; Chuchu Feng; Jialu Lin; Lidong Cheng; Chengjun Wang; Yuegang Zuo (Environmental Science and Pollution Research, 2017)

Association analysis between HFM1 variations and idiopathic azoospermia or severe oligozoospermia in Chinese Men - Wenxiang Zhang; Xiaomin Song; Feng Ni; Jinbao Cheng; Bai-Lin Wu; Hong Jiang (Science China Life Sciences, 2017)

Cellulase with high β-glucosidase activity by Penicillium oxalicum under solid state fermentation and its use in hydrolysis of cassava residue - Lin-Hui Su; Shuai Zhao; Sui-Xin Jiang; Xu-Zhong Liao; Cheng-Jie Duan; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2017)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

Characterization of the spatial variability of soil available zinc at various sampling densities using grouped soil type information - Xiao-Dong Song; Gan-Lin Zhang; Feng Liu; De-Cheng Li; Yu-Guo Zhao (Environmental Monitoring and Assessment, 2016)

Controlling effects of surface crusts on water infiltration in an arid desert area of Northwest China - Jin-Ling Yang; Gan-Lin Zhang; Fei Yang; Ren-Min Yang; Chen Yi; De-Cheng Li; Yu-Guo Zhao; Feng Liu (Journal of Soils and Sediments, 2016)

Outlining a stepwise, multi-parameter debris flow monitoring and warning system: an example of application in Aizi Valley, China - Ning-sheng Chen; Javed Iqbal Tanoli; Gui-sheng Hu; Feng-niang Wang; Cheng-lin Yang; Hai-tao Ding; Na He; Tao Wang (Journal of Mountain Science, 2016)

Interleukin-17A Acts to Maintain Neuropathic Pain Through Activation of CaMKII/CREB Signaling in Spinal Neurons - Cheng-ye Yao; Ze-lin Weng; Jian-cheng Zhang; Tao Feng; Yun Lin; Shanglong Yao (Molecular Neurobiology, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Calreticulin Regulates VEGF-A in Neuroblastoma Cells - Wen-Chin Weng; Kuan-Hung Lin; Pei-Yi Wu; Yi-Chien Lu; Yi-Cheng Weng; Bo-Jeng Wang; Yung-Feng Liao; Wen-Ming Hsu; Wang-Tso Lee; Hsinyu Lee (Molecular Neurobiology, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Cloning of a caffeoyl-coenzyme A O-methyltransferase from Camellia sinensis and analysis of its catalytic activity - Yue Zhang; Hai-peng Lv; Cheng-ying Ma; Li Guo; Jun-feng Tan; Qun-hua Peng; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Seasonal characteristics and tetrodotoxin-producing ability of bacteria in gastropod Oliva hirasei - Chun-Lan Lin; Ya-Jung Wu; Wen-Feng Lin; Cheng-Hong Hsieh; You-Liang Hsieh; Deng-Fwu Hwang (Hydrobiologia, 2014)

Modified high-intensity interval training increases peak cardiac power output in patients with heart failure - Shu-Chun Huang; Mei-Kuen Wong; Pyng-Jing Lin; Feng-Chun Tsai; Tieh-cheng Fu; Ming-Shien Wen; Chi-Tai Kuo; Jong-Shyan Wang (European Journal of Applied Physiology, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Interactive influence of light intensity and soil fertility on root-associated arbuscular mycorrhizal fungi - Guoxi Shi; Yongjun Liu; Nancy Collins Johnson; Pål Axel Olsson; Lin Mao; Gang Cheng; Shengjing Jiang; Lizhe An; Guozhen Du; Huyuan Feng (Plant and Soil, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Transcriptome and Gene Expression Analysis of an Oleaginous Diatom Under Different Salinity Conditions - Ruo-lin Cheng; Jia Feng; Bing-Xin Zhang; Yun Huang; Jun Cheng; Chuan-Xi Zhang (BioEnergy Research, 2014)

Wheat cultivars form distinctive communities of root-associated arbuscular mycorrhiza in a conventional agroecosystem - Lin Mao; Yongjun Liu; Guoxi Shi; Shengjing Jiang; Gang Cheng; Xingmao Li; Lizhe An; Huyuan Feng (Plant and Soil, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

The roles of two transcription factors, ABI4 and CBFA, in ABA and plastid signalling and stress responses - Zhong-Wei Zhang; Ling-Yang Feng; Jian Cheng; He Tang; Fei Xu; Feng Zhu; Zhong-Yi Zhao; Ming Yuan; Yang-Er Chen; Jian-Hui Wang; Shu Yuan; Hong-Hui Lin (Plant Molecular Biology, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Potential Prevention and Treatment of Maifanite for Alzheimer's Disease Based on Behavior Test, Oxidative Stress Assay, and Trace Element Analysis in Hippocampus of Aβ(25–35)-Induced AD Rats - Ling-Feng Jiang; Hai-Lin Liao; Hong-Miao Huang; Li-Xia Zhou; Ling Li; Shi-Xian Cheng; Cheng-Zhi Du (Biological Trace Element Research, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

BEAK LIKE SPIKELET1 is Required for Lateral Development of Lemma and Palea in Rice - Xiaoding Ma; Zhijun Cheng; Fuqing Wu; Mingna Jin; Liguo Zhang; Feng Zhou; Jiulin Wang; Kunneng Zhou; Jian Ma; Qibing Lin; Cailin Lei; Jianmin Wan (Plant Molecular Biology Reporter, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

The antidepressant effect of secoisolariciresinol, a lignan-type phytoestrogen constituent of flaxseed, on ovariectomized mice - Ying-Feng Wang; Zhi-Kun Xu; Dong-Hui Yang; Hai-Yan Yao; Bao-Shan Ku; Xiao-Qing Ma; Cheng-Zhi Wang; Shu-Lin Liu; Shao-Qing Cai (Journal of Natural Medicines, 2013)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

Niacin improves ischemia-induced neovascularization in diabetic mice by enhancement of endothelial progenitor cell functions independent of changes in plasma lipids - Po-Hsun Huang; Chih-Pei Lin; Chao-Hung Wang; Chia-Hung Chiang; Hsiao-Ya Tsai; Jia-Shiong Chen; Feng-Yen Lin; Hsin-Bang Leu; Tao-Cheng Wu; Jaw-Wen Chen; Shing-Jong Lin (Angiogenesis, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

Caffeine’s effect on intermittent sprint cycling performance with different rest intervals - Chia-Lun Lee; Ching-Feng Cheng; Jung-Charng Lin; Hsin-Wei Huang (European Journal of Applied Physiology, 2012)

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan - Nai-Tong Yu; Yu-Liang Zhang; Tuan-Cheng Feng; Jian-Hua Wang; Mahesh Kulye; Wen-Jun Yang; Zhan-Song Lin; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Chronic alcohol intake-induced oxidative stress and apoptosis: role of CYP2E1 and calpain-1 in alcoholic cardiomyopathy - Ling Jing; Cheng-mei Jin; Shan-shan Li; Feng-min Zhang; Lin Yuan; Wei-min Li; Ying Sang; Shuang Li; Li-jun Zhou (Molecular and Cellular Biochemistry, 2012)

Rapid change of AM fungal community in a rain-fed wheat field with short-term plastic film mulching practice - Yongjun Liu; Lin Mao; Xinhua He; Gang Cheng; Xiaojun Ma; Lizhe An; Huyuan Feng (Mycorrhiza, 2012)

Novel human BTB/POZ domain-containing zinc finger protein ZBTB1 inhibits transcriptional activities of CRE - Qingmei Liu; Feng Yao; Minghua Wang; Bin Zhou; Hongxia Cheng; Weiping Wang; Li Jin; Qiang Lin; Jiu-Cun Wang (Molecular and Cellular Biochemistry, 2011)

The relationship between competitive ability and yield stability in an old and a modern winter wheat cultivar - Yan Fang; Lin Liu; Bing-Cheng Xu; Feng-Min Li (Plant and Soil, 2011)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Quantitative Analysis of Quercetin in Euphorbia helioscopia L by RP-HPLC - Hai Peng Liu; Xiao Feng Shi; You Cheng Zhang; Zhong Xin Li; Lin Zhang; Zhe Yuan Wang (Cell Biochemistry and Biophysics, 2011)

Effect of caffeine ingestion after creatine supplementation on intermittent high-intensity sprint performance - Chia-Lun Lee; Jung-Charng Lin; Ching-Feng Cheng (European Journal of Applied Physiology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

Celecoxib induces heme oxygenase-1 expression in macrophages and vascular smooth muscle cells via ROS-dependent signaling pathway - Jang-Shiun Wang; Feng-Ming Ho; Hao-Cheng Kang; Wan-Wan Lin; Kuo-Chin Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

A GIS-based Decision Support System for Typhoon Emergency Response in Taiwan - Ming-Hsi Hsu; Albert S. Chen; Liang-Chun Chen; Cheng-Shang Lee; Feng-Tyan Lin; Chen-Jia Huang (Geotechnical and Geological Engineering, 2011)

Characterization of a male sterile mutant from progeny of a transgenic plant containing a leaf senescence-inhibition gene in wheat - Ya-Jun Xi; Xue-Feng Ma; Huan Zhong; Shu-Dong Liu; Zhu-Lin Wang; Yang-Yang Song; Cheng-Hui Zhao (Euphytica, 2011)

VKORC1-1639G>A, CYP2C9, EPHX1691A>G genotype, body weight, and age are important predictors for warfarin maintenance doses in patients with mechanical heart valve prostheses in southwest China - Qiang Gu; Yan Kong; Jörn Schneede; Ying-Bin Xiao; Lin Chen; Qian-Jin Zhong; Xue-Feng Wang; Jia Hao; Bai-Cheng Chen; Jing-Jin Chen (European Journal of Clinical Pharmacology, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Construction of a recombinant adenovirus vector expressing IL-18BP/IL-4 fusion gene and the anti-inflammatory effect induced by this gene on lipopolysaccharide-stimulated synovial fibroblasts - Hang-Ping Yao; Yun Qian; Xue-Ting Shao; Zhe-Rong Xu; Lin-Fang Cheng; Lei Feng; Nan-Ping Wu; Yun-Mei Yang (Inflammation Research, 2010)

A chaos-based visual encryption mechanism for clinical EEG signals - Chin-Feng Lin; Cheng-Hsing Chung; Jia-Hui Lin (Medical & Biological Engineering & Computing, 2009)

A ThCAP gene from Tamarix hispida confers cold tolerance in transgenic Populus (P. davidiana × P. bolleana) - Xiao-Hong Guo; Jing Jiang; Shi-Jie Lin; Bai-Chen Wang; Yu-Cheng Wang; Gui-Feng Liu; Chuan-Ping Yang (Biotechnology Letters, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Isolation and characterization of microsatellite loci in the commercially important mudshrimp Austinogebia edulis (Upogebiidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Hung-Du Lin; Tin-Yam Chan; Cheng-Yu Hung; Feng-Jiau Lin (Conservation Genetics, 2008)

Seasonal change and correlation with environmental parameters for 2-MIB in Feng-Shen Reservoir, Taiwan - Shu-Chu Tung; Tsair-Fuh Lin; Feng-Cheng Yang; Chia-Lin Liu (Environmental Monitoring and Assessment, 2008)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Apoptosis induced by ardipusilloside III through BAD dephosphorylation and cleavage in human glioblastoma U251MG cells - Hong Lin; Xiang Zhang; Guang Cheng; Hai-Feng Tang; Wei Zhang; Hai-Ning Zhen; Jin-Xiang Cheng; Bo-Lin Liu; Wei-Dong Cao; Wen-Peng Dong; Peng Wang (Apoptosis, 2008)

Callus of Securinega suffruticosa , a cell line accumulates dextro Securinega alkaloids - Wei Yuan; Ping Zhu; Kedi Cheng; Chao Meng; Lin Ma; Feng Wu; Huixin Zhu (Natural Product Research, 2007)

Changes of Src-suppressed C kinase substrate expression in cytokine induced reactive C6 glioma cells - Lin-Lin Sun; Chun Cheng; Hai-Ou Liu; Feng Xiao; Jing Qin; Xiao-Yi Shao; Ai-Guo Shen (Neuroscience Bulletin, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

The Endo-β-Mannanase gene families in Arabidopsis, rice, and poplar - Joshua S. Yuan; Xiaohan Yang; Jingru Lai; Hong Lin; Zong-Ming Cheng; Hiroyuki Nonogaki; Feng Chen (Functional & Integrative Genomics, 2006)

Spatial and temporal dynamics of soil organic carbon in reserved desertification area - Shu-lan Cheng; Hua Ouyang; Hai-shan Niu; Lin Wang; Feng Zhang; Jun-qin Gao; Yu-qiang Tian (Chinese Geographical Science, 2004)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

cDNA cloning and characterization of a plant protein that may be associated with the harpinPSS-mediated hypersensitive response - Cheng-hsien Chen; Hao-jan Lin; Mang-jye Ger; David Chow; Teng-yung Feng (Plant Molecular Biology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)